Ընդդիմությունը որպես քաղաքական համակարգի ինստիտուտ. էությունը և ձևերը - Գայանե Մխոյան (ՀՀ ԳԱԱ հրատ.)
Политическая оппозиция является одной из характеристик современных политических систем. Она играет важную роль для политической системы. Оппозиция способствует нормальному и стабильному развитию системы, является институтом, предотвращающим окостенение системы. В статье обсуждается сущность оппозиции, распространенные в политологической литературе определения, ее роль в политической системе, условия, необходимые для формирования оппозиции, ее функции и типология. Political opposition is one of the characteristics of modern political system. It plays an important role in the political system. The opposition contributes to the normal and stable development of the system and acts as an institute preventing the ossification of the latter. The current article discusses the essence of opposition, its common definitions in politological literature, its role in the political system, conditions necessary for the formation of opposition, its functions and typology.
Keywords: Political Science